2013
DOI: 10.1159/000355393
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Interleukin-4/Signal Transducer and Activator of Transcription 6 Signaling Pathway and Homeodomain-Interacting Protein Kinase 2 Production by Tonsillar Mononuclear Cells in IgA Nephropathy

Abstract: Background/Aim: Clinical development and exacerbation of IgA nephropathy (IgAN) are frequently preceded by episodes of upper respiratory tract infection such as tonsillitis. This study aimed to determine the role of the interleukin-4 (IL-4)/signal transducer and activator of transcription 6 (STAT6) signaling pathway and homeodomain-interacting protein kinase 2 (HIPK2) in aberrant IgA1 O-glycosylation production, and identify potential therapeutic targets in IgAN. Methods: Expression levels of IL-4, STAT6, core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…[42][43][44][45] Reports showed abnormal glycosylation of tonsillar IgA 46,47 and aberrant cytokine profiles in tonsillar B cells, leading to the underglycosylation of IgA1 in patients with IgAN. [48][49][50][51] Because total IgA is decreased by approximately 10% on average after tonsillectomy alone in patients with IgAN 27 and because patients who showed a large decrease of serum IgA after the tonsillectomy had better clinical outcome, the palatine tonsil was hypothesized to be a major delivery source of nephritogenic IgA. 27 Indeed, we recently showed that Gd-IgA1 was significantly decreased after tonsillectomy in patients with IgAN, who also showed a significant improvement in urinalysis just after tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…[42][43][44][45] Reports showed abnormal glycosylation of tonsillar IgA 46,47 and aberrant cytokine profiles in tonsillar B cells, leading to the underglycosylation of IgA1 in patients with IgAN. [48][49][50][51] Because total IgA is decreased by approximately 10% on average after tonsillectomy alone in patients with IgAN 27 and because patients who showed a large decrease of serum IgA after the tonsillectomy had better clinical outcome, the palatine tonsil was hypothesized to be a major delivery source of nephritogenic IgA. 27 Indeed, we recently showed that Gd-IgA1 was significantly decreased after tonsillectomy in patients with IgAN, who also showed a significant improvement in urinalysis just after tonsillectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot was performed according to our previous procedures [23]. Membranes were incubated with the following primary antibodies, respectively: rabbit antibody to caspase 3, caspase 9 (1:500 Cell Signaling Technology, Beverly, Mass., USA), Nrf2 (1:200 Biorbyt, Cambridge, UK), and NLRP3 (1:1,000 MyBioSource, LLC, San Diego, Calif., USA).…”
Section: Methodsmentioning
confidence: 99%
“…Lysates of kidney tissue were prepared, as described previously [23]. All the antibodies in Western blot were purchased from Cell Signaling Technology Inc. (Beverly, MA, USA), and the dilute concentration was based on antibody instruction.…”
Section: Methodsmentioning
confidence: 99%